Impact of 21-gene recurrence score testing on adjuvant chemotherapy decision making in older patients with breast cancer. Issue 5 (June 2020) - Zeng, Yufei; Gao, Weiqi; Lin, Lin; Chen, Xiaosong; Shen, Kunwei
Abstract: Purpose: To evaluate the role of 21-gene recurrence score (RS) assay in adjuvant chemotherapy decision-making among older patients with early breast cancer. Methods: Consecutive hormonal receptor-positive, aged ≥60 patients with breast cancer were enrolled from Shanghai Ruijin Hospital between January 2014 and December 2017. Treatment decisions were made by multi-disciplinary team (MDT) before and after 21-gene RS testing, and the actual treatment for each patient was also analyzed. Results: A total of 511 patients were enrolled, with 331 (64.8%) aged between 60 and 69, 140 (27.4%) between 70 and 79, and 40 (7.8%) over 80 years. There were 138 (27.0%), 287 (56.2%), and 86 (16.8%) patients classified as low, intermediate, and high risk RS, respectively. Multivariable analysis demonstrated that age, tumor stage, nodal status, PR expression, Ki-67, and 21-gene RS were independent impact factors for chemotherapy recommendations (P < .05). Patients with high risk RS and intermediate risk RS (both P < .001) were more often recommended to receive chemotherapy than patients with low risk RS. Treatment recommendations changed in 74 (14.5%) patients after 21-gene RS testing: 17 (3.3%) from chemotherapy to no chemotherapy and 57 (11.2%) from no chemotherapy to chemotherapy. Overall compliance rate to MDT recommendation after 21-gene RS testing was 95.7%. Conclusion: An intermediate and/or high risk 21-gene RS assay was independently associated with receiving adjuvant chemotherapy among older patients with breast cancer. However, it showed a limited impact on adjuvant chemotherapy decision-making. After 21-gene RS testing, compliance with MDT recommendation was relatively high in older patients with breast cancer.